Sperm and histological evaluation of testis and epididymis of canine naturally infected by Brucella canis - Volkweis, Fabiana; Blume, Helio; Santos Junior, Helvecio Leal; Lazzari, Andrea Maria; Mulinari, Fernanda (Pubvet, 2020)
Canine brucellosis is a chronic infectious disease that directly affects the male and female reproductive tract. This study aims to evaluate and compare the damage caused by this infection in male canines. Four canines positive for canine brucellosis were selected, confirmed by blood culture, IDGA and PCR tests. They were submitted to seminal analysis, posterior orchiectomy and histological evaluation of the testicles. The seminal analysis showed morphological changes compatible with the disease. On histology a moderate interstitial multifocal lymphohistiocytic infiltrate was visualized in the epididymis and in the teste’s vacuolar degeneration.
Keywords: canine brucellosis; seminal evaluation; infertility